2017
DOI: 10.1186/s40248-017-0088-1
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the mucoactive activity and clinical efficacy of bromhexine

Abstract: Since its introduction to the market in 1963, bromhexine, an over-the-counter drug, has been investigated for its activity in animal models and in humans with diverse respiratory conditions. Bromhexine is a derivate of the Adhatoda vasica plant used in some countries for the treatment of various respiratory diseases. Bromhexine has been found to enhance the secretion of various mucus components by modifying the physicochemical characteristics of mucus. These changes, in turn, increase mucociliary clearance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 32 publications
(43 reference statements)
0
26
0
2
Order By: Relevance
“…[ 14 ] Bromhexine can reduce sputum viscosity, promote lung ventilation and expectoration, and remove virus residues. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] Bromhexine can reduce sputum viscosity, promote lung ventilation and expectoration, and remove virus residues. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%
“…Both AMB and BHH have been used in the clinic for treatment of respiratory conditions and are extensively studied, because of their multiple pharmacologic effects and safety profile [20][21][22][23][24] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their impact on lung physiology and function with regards to mucociliary clearance, mucokinetic properties, and stimulation of surfactant production, they have also been shown to elicit anti-inflammatory, antioxidative and anesthetic effects [20][21][22][23][24] Additional studies have reported that both compounds induce cellular autophagic-lysosome pathway [29][30][31] . Reports have also shown the involvement of AMB in modulation of the homeostasis of ions such as sodium, hydrogen, and calcium 33,51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations